The Success of Meat and Fish Sellers Resilience Strategies in the post COVID-19 (Study Case: Market in Peri-Urban Area of Surakarta) - Kiat, Umar El Izzudin; Putra, Ramadhany Ade Tonisyach; Januar, Rino Dzul Qad; Alfath, Muhammad Widad; Ramadhani, Fahrizza Arrayan; Audi, Fresilia; Arum, Shofa (Universitas Muhammadiyah Surakarta, 2024)
The Covid 19 pandemic has had a negative impact on economic sectors, such as decreasing sales. Traditional markets located in the peripheral areas of Surakarta City are the main economic source of the people living in the area. To overcome the impact of the Covid- 19 pandemic on the economic sector in traditional markets, sales strategies are needed to remain viable during the Covid-19 pandemic. Such as continuing to sell, selling online, side jobs. The aim of this research was to analyze the sales strategies used by fish and meat traders during the Covid-19 pandemic to survive. The method used in this research is purposive sampling method with primary data collection using structured interviews and in-depth interviews. From the research results, the strategy with the largest percentage uses the strategy of continuing to sell and selling online.